2019
DOI: 10.1093/ije/dyz205
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots of childhood obesity in a large metropolitan area: does neighbourhood social and built environment play a part?

Abstract: Background Effective place-based interventions for childhood obesity call for the recognition of the high-risk neighbourhoods and an understanding of the determinants present locally. However, such an approach is uncommon. In this study, we identified neighbourhoods with elevated prevalence of childhood obesity (‘hotspots’) in the Porto Metropolitan Area and investigated to what extent the socio-economic and built environment characteristics of the neighbourhoods explained such hotspots. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…GAMs are extensions of typical linear regressions models (e.g., logistic regression model for binary data) that include smoothed terms that allow for the relaxing of typical assumptions of linearity between predictors and outcomes [40]. In the field of spatial epidemiology, mixed-mode GAMs, in which only location coordinates are non-parametrically smoothed, whereas other covariates keep a form of linear parametric prediction [36], have been used to investigate the geographic variation of diseases [36,[41][42][43][44][45][46][47]. The below model was used to calculate ORs in this study:…”
Section: Discussionmentioning
confidence: 99%
“…GAMs are extensions of typical linear regressions models (e.g., logistic regression model for binary data) that include smoothed terms that allow for the relaxing of typical assumptions of linearity between predictors and outcomes [40]. In the field of spatial epidemiology, mixed-mode GAMs, in which only location coordinates are non-parametrically smoothed, whereas other covariates keep a form of linear parametric prediction [36], have been used to investigate the geographic variation of diseases [36,[41][42][43][44][45][46][47]. The below model was used to calculate ORs in this study:…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, obesity is a risk factor for acne, which implies that types and numbers of restaurants around the residential and work location of people could be related to their obesity. A number of studies in the US ( 139 ), New York ( 105 ), Utah ( 106 ), the UK ( 13 , 140 ), Porto ( 104 ), New Orleans ( 141 ), and China ( 142 ) showed higher fast food restaurant density was significantly associated with higher obesity rates among students. Therefore, an increased number of fast food restaurants near the address may increase the risk of obesity, which may indirectly affect the occurrence of acne.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a growing number of studies have focused on the impact of built environment on health (Table 4 in Appendix), especially those chronic diseases such as obesity (13), cardiovascular disease (15) and mental health (14). Studies indicated that obesity was positively associated with population density and the availability of fast-food outlets from the people's residence (104)(105)(106)(107)(108). Moreover, other studies also found the incidence of cardiovascular disease was significantly higher with more fast-food outlets than areas with no fast-food outlets (15,109).…”
Section: Built Environmental Factorsmentioning
confidence: 99%
“…These locals of eating out are more appeal for the more vulnerable due to lower food prices, especially by spending per unit of energy (46) and also because they are possibly exposed to a high density of fast-food outlets in the places of residence (43,45) . In a study, using data from the population-based cohort Generation XXI was also found that neighbourhood deprivation and paedestrian access to fast-food outlets could increase the prevalence of obesity in children with 7 years (47) . This double burden, higher exposure to fast-food outlets and low income represent an additive effect for lower diet quality and can be a possible explanation for our results.…”
Section: Discussionmentioning
confidence: 99%